Peran UMKM Lokal dalam Menguatkan Ekonomi Pesantren melalui Kemitraan Berbasis Syariah: Studi di Pondok Pesantren Syubbanul Wathon Magelang - Muna, Fauzul; Pudail, M.; Aini, Qurotul (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2025)
This study examines the role of local MSMEs in strengthening the economic independence of Islamic boarding schools through sharia-based partnerships at Pondok Pesantren Syubbanul Wathon, Magelang. The research employed a case study with a qualitative approach using interviews, observations, and documentation. Findings reveal that the partnership between the pesantren and local MSMEs is implemented through a mudharabah-based consignment system, where MSMEs act as product suppliers and the pesantren provides market access via its canteen unit. This partnership generates mutual benefits: the pesantren secures a sustainable internal source of income, while MSMEs gain access to a stable market. Furthermore, students actively participate in canteen management, acquiring entrepreneurial skills relevant to current economic demands. Thus, this collaboration not only strengthens the pesantren’s economic independence and empowers local MSMEs but also fosters social cohesion by enhancing the relationship between the pesantren and surrounding communities.